2011
DOI: 10.1063/1.3609277
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and structural properties of the high density Gaussian core model

Abstract: We numerically study thermodynamic and structural properties of the one-component Gaussian core model at very high densities. The solid-fluid phase boundary is carefully determined. We find that the density dependence of both the freezing and melting temperatures obey the asymptotic relation, log T f , log T m ∝ −ρ 2/3 , where ρ is the number density, which is consistent with Stillinger's conjecture. Thermodynamic quantities such as the energy and pressure and the structural functions such as the static struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
(136 reference statements)
2
22
0
Order By: Relevance
“…(A1)). Indeed, we found S(k → 0) ≈ 10 −6 at the temperatures we studied [26]. Furthermore, χ 2 ρ in Eq.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…(A1)). Indeed, we found S(k → 0) ≈ 10 −6 at the temperatures we studied [26]. Furthermore, χ 2 ρ in Eq.…”
Section: Discussionmentioning
confidence: 79%
“…The crystallization kinetics is very slow and virtually negligible in our simulations [23,24]. We note that the density is much higher than ρ ≈ 0.24, the re-entrant melting density of GCM [26][27][28]. In the low density limit, the GCM approaches asymptotyically the three-dimensional hard sphere model [21].…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the same line of reasoning, one could wonder whether glassy effects could come into play upon lowering the density even more. Indeed it has been observed that in soft systems, the melting transition and the glass transition are re-entrant, meaning that one can observe the melting of the crystal or of the glass upon densifying the system [38,47,48]. The perturbative expansion that we use here is likely to be valid only at even higher densities, since only non-perturbative calculations such as Mode-Coupling Theory have so far been able to capture glassy behaviors in the dynamics [49,50].…”
Section: Resultsmentioning
confidence: 99%
“…The Gaussian-core model (GCM), in which particles interact with a a purely repulsive Gaussian pair potential, v 2 (r) = exp[−(r/σ) 2 ], was introduced by Stillinger [364] as a simple model to mimic effective pair interactions between the centers of mass of two polymer chains. Since then, the GCM has been investigated by many groups [363,[365][366][367]. Zachary, Stillinger and Torquato [363] studied the liquid states of this model in R d in various approximations and arbitrary dimensions.…”
Section: Polymeric Materials: Liquid State and Glass Formationmentioning
confidence: 99%